Desain Manajemen Rantai Pasok Daging Ayam Halal pada Rumah Potong Ayam (Studi Kasus pada Distributor Ayam Broiler di Kabupaten Cilacap) - Hayunda Nur Annisa; Harwati Harwati (LPPM Institut Pendidikan Nusantara Global, 2026)
The objective of this study is to evaluate the performance of the halal broiler chicken meat supply chain at UD Mustika through the implementation of the Balanced Scorecard (BSC) integrated with Key Performance Indicators (KPI) and the Traffic Light System (TLS), in accordance with HAS 23000 and HAS 23103. Using a quantitative method, data were collected through observation, interviews, and questionnaires. Performance indicators were assessed based on achievement levels and classified using TLS to identify conditions and prioritize improvements. The research framework included problem identification, determination of halal performance indicators, measurement and classification, gap analysis, and managerial implications for sustainability. Results show that overall supply chain performance is generally good, with the highest achievements in internal business process and customer perspectives, while financial and learning & growth perspectives show red and yellow indicators, requiring managerial attention. Strengthening human resource competencies and halal process innovation is key to improving financial performance and sustaining the halal assurance system.